Entrepreneurial self-efficacy and competencies:entrepreneurs' embedded resources - Dzulkifli Mukhtar (2010)
In a new venture creation process,entreneurs need to have a significant level of self-confidence and also ability in performing specific entrepreneurial tasks. These elements are considered as embedded resources for the entrepreneurs. It is important to recognize these two elements at the early stage of the new venture creation process because they can influence entrepreneurs thinking, behavoiur and also action